Liability of Notaries for Debts and Receivables Made With the Deed of Sale and Purchase Binding Agreement and Power of Attorney for Sale Debt Guarantee Certificate - Winda Kusuma, Reza Olivia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
The results showed that the deed of acknowledgment of debt based on the binding sale and purchase agreement and the selling power of attorney was canceled by the judge, namely the mortgage right in the engagement is the right that gives the mortgage holder the rights to hold the collateral right if there is a default, the mortgage holder can apply for a security confiscation in accordance with the law. The agreement according to article 1320 is a legal agreement made between the two parties whose contents are the rights and obligations of each. The terms of the agreement are subjective terms and objective conditions. The position of the case and the position of the case and the judge's decision related to the binding sale and purchase agreement and the power of attorney to sell, namely the results of the trial by the Panel of Judges, the identity of the defendant, namely Tri Agus Heryono, SH bin Ruyono Sumowidigd, the judge was of the opinion that there was no in persona error in the indictment of the Public Prosecutor, so that the element of whoever was fulfilled. What is meant by benefiting oneself or others is that the maker or other person enjoys the results of their actions either directly or indirectly. What is meant by unlawful means is that the act is carried out in a way that is contrary to the law.Keywords: Accountability; Certificate; Guarantee; Payable.